Endo 180 participates in collagen remodeling of the periodontal ligament during orthodontic tooth movement - Liyuan Chen; Danqing He; Zixin Li; Shengjie Cui; Min Yu; Zimo Zhao; Yuetong Chen; Jiayi Song; Nan Jiang; Huajie Yu; Yan Liu (BMC Oral Health)
Abstract Background Orthodontic tooth movement (OTM) relies on the remodeling of periodontal tissues, including the periodontal ligament (PDL) and alveolar bone. Collagen remodeling plays a crucial role during this process, allowing for the necessary changes in the PDL’s structure and function. Endo180, an urokinase plasminogen activator receptor-associated protein, is a transmembrane receptor regulated collagen remodeling. This study aims to investigate whether and how Endo180 participates in collagen remodeling within the PDL during OTM. Materials and methods A mechanical force-induced OTM rat model was established using a closed coiled spring to mesially move the right maxillary first molar. The distance of OTM was examined by micro-computed tomography (micro-CT). The collagen remodeling within the PDL was assessed using atomic force microscope (AFM), Hematoxylin-Eosin (HE) staining and Masson staining. Protein expressions of Endo180, collagen I (COL I) and collagen III (COL III) were analyzed via immunofluorescence staining. Additionally, the mRNA expressions of Endo180, COL I, and COL III in force-induced PDL cells were examined by RT-qPCR in vitro. To further illustrate the role of Endo180 in regulating COL I and COL III expressions, Endo180 siRNA (siEndo) was applied to force-stimulated PDL cells. Results Force application increased OTM distance and disrupted collagen fiber organization, with a greater decrease in collagen elastic modulus on the mesial side than on the distal side of the PDL. After 7 days of force application, Endo180 and COL III expressions significantly increased in PDL tissues, while COL I expression decreased in PDL tissues. Compressive force loading in vitro upregulated the mRNA expressions of Endo180 and COL III, but downregulated COL I mRNA expression. Notably, Endo180 knockdown using siRNA suppressed force-induced COL III expression while restoring the downregulated COL I expression under compressive force stimuli. Conclusion Force-induced Endo180 expression modulates collagen remodeling in PDL during OTM by upregulating COL III and downregulating COL I. This collagen reorganization facilitates efficient tooth movement, highlighting Endo180 as a potential therapeutic target to optimize orthodontic treatment outcomes.